Determinants of Net Asset Value of Sharia Equity Mutual Funds in Indonesia - Hazami, Baehaki; Endri, Endri (Devotion : Journal of Research and Community Service, 2024)
This research aims to analyze the influence of the BI 7 days repo rate, inflation, exchange rate, JKSE, mutual fund size, stock selection skill and market timing ability on the net asset value of sharia equity mutual funds in Indonesia. The research was divided into 3 period results, namely overall (2017-2022), before the Covid-19 pandemic (2017-2019), and during the Covid-19 pandemic (2020-2022). Data processing uses Eviews 12. The method used is the Random Effect Model (REM) with the analysis model using Generalized Least Square (GLS). The results of this research state that over all the BI 7 days repo rate has a significant positive effect, however in the period before the pandemic the effect was significantly negative, whereas during the pandemic there was no effect. Inflation in whole period and when a pandemic has no effect, but in the period before the pandemic it has a significant positive effect. The exchange rate in whole period has a significantly negative effect, but in the period before the pandemic it has a significantly positive effect, whereas during the pandemic it has no effect. The JKSE in whole period has no effect, but in the period before and during the pandemic it had a significant positive influence. Mutual fund size in whole period and during the pandemic has a significant positive effect, but in the period before the pandemic it has no effect, stock selection skill in whole period, in the period before and during the pandemic has a significant positive effect. market timing ability in whole period, in the period before and during the pandemic had a significant positive effect. Differences in results in a period are due to changes in economic conditions in Indonesia.